MaxEnt modeling to show patterns of coastal habitats of reef-associated fish in the South and East China Seas - Wang, Jia; Tabeta, Shigeru (Frontiers in Ecology and Evolution, 2023)
Reef-associated fish, one of the most economically and ecologically crucial functional groups, are a key source of protein for coastal residents. However, human activities and climate change have harmed their habitats; in two of the most important large marine ecosystems, the South China Sea (SCS) and East China Sea (ECS), the situation is dire. Based on high-spatial-resolution environmental factors and fish presence data, we modeled the potentially suitable habitats of reef-associated fish in the SCS and ECS between 1993 and 2019, estimated the importance of environmental factors on habitat distribution, and identified seasonal variation and distribution shifts over recent decades. The results show that moderate and highly suitable areas for reef-associated fish in the region total 360,000 km2. We found that sea body temperature, chlorophyll-α concentration, and seawater salinity are crucial for determining the distribution of reef-associated fish; moreover, reef-associated fish are also sensitive to seawater temperature in winter. Our research shows that reef-associated fish in the region have a wide distribution near coastlines, but suitable areas have decreased owing to environmental changes within the region. The findings of this study offer a valuable resource for developing fishery management and conservation strategies for this important functional group.